Examining the impact of bank’s risks to Islamic banks’ profitability - Priyonggo Suseno; Omar Bamahriz (Universitas Islam Indonesia, 2017)
This paper analyzes the impact of banks' risk to the profitability of Islamic banks and to identify what risks play the non-trivial role. To this objective, 75 Islamic banks in 24 countries in 2015 have been studied. A series of bank risks, industry-specific and macroeconomic indicators are combined to explain the profitability of Islamic banking as measured by Return on Average Assets (ROAA), Return on Average Equity (ROAE), and Value Added (VA). The bank risks comprise credit risk, insolvency risk, liquidity risk, and operational risk. Having used robust linear regressions, the results indicate that all four types of risk influence bank's profitability. Operational risk is the risk that plays the most important role in influencing banks' profitability, whether measured by ROAA, ROAE or profit before taxes over the total asset (PBTTA). On the other hand, credit risk, liquidity, and insolvency do not conclusively increase or decrease Islamic bank profitability. Macroeconomic conditions, measured by inflation, actually has a positive impact on the profitability of Islamic banks. This indicates that operational risks and macroeconomic stability should be given primary attention in increasing bank's profitability.